2006
DOI: 10.5326/0420071
|View full text |Cite
|
Sign up to set email alerts
|

Polyostotic Lymphoma With Vertebral Involvement and Spinal Extradural Compression in a Dog

Abstract: A 10-year-old, male, mixed-breed dog that developed cervical pain and neurological deficits was diagnosed with primary lymphoma of the second cervical vertebra. The cervical lesion was not surgically resectable. A dorsal cervical hemilaminectomy was performed to provide temporary decompression. The dog had complete pain relief after surgery but was euthanized 6 weeks later with recurrent clinical signs and evidence of lymphoma in the right femur.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
1
5

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(35 citation statements)
references
References 12 publications
1
28
1
5
Order By: Relevance
“…Only one previous case of confirmed extradural T‐cell lymphoma has been reported to receive treatment consisting of cytoreductive surgery . However, in that case, chemotherapy was declined and, following an initial period of improvement, the dog was euthanized due to tumor recurrence confirmed on myelography 6 weeks postoperatively.…”
Section: Discussionmentioning
confidence: 99%
“…Only one previous case of confirmed extradural T‐cell lymphoma has been reported to receive treatment consisting of cytoreductive surgery . However, in that case, chemotherapy was declined and, following an initial period of improvement, the dog was euthanized due to tumor recurrence confirmed on myelography 6 weeks postoperatively.…”
Section: Discussionmentioning
confidence: 99%
“…1,6 There are few published reports about dogs of lymphoma where lytic bone lesions are the prominent feature of the disease. These cases are perhaps best referred to as lymphoma mainly affecting bone rather than as primary lymphoma of bone.…”
Section: ]/Dept-list)>mentioning
confidence: 99%
“…7 In a recent report of a polyostotic lymphoma with vertebral involvement in a dog, immunohistochemical stains indicated a T-cell immunophenotype. 6 Peripheral T-cell lymphoma with acquired systemic osteosclerosis has been described in a human patient. 4 Osteosclerosis was interpreted as a paraneoplastic syndrome, due to secretion of an osteoblast-activating factor by the T-cell lymphoma.…”
Section: ]/Dept-list)>mentioning
confidence: 99%
“…It had been observed that OL may sometimes recur in bone exclusively, both in human beings (1) and in dogs (9). In some patients, multiple bony sites are affected in the absence of soft tissue disease, raising the possibility that a homing process was occurring.…”
Section: Introductionmentioning
confidence: 98%